Mitochondrial isocitrate dehydrogenase is inactivated upon oxidation and reactivated by thioredoxin-dependent reduction in Arabidopsis - Yoshida, Keisuke; Hisabori, Toru (Frontiers in Environmental Science, 2014)
Regulation of mitochondrial metabolism is essential for ensuring cellular growth and maintenance in plants. Based on redox-proteomics analysis, several proteins involved in diverse mitochondrial reactions have been identified as potential redox-regulated proteins. NAD+-dependent isocitrate dehydrogenase (IDH), a key enzyme in the tricarboxylic acid (TCA) cycle, is one such candidate. In this study, we investigated the redox regulation mechanisms of IDH by biochemical procedures. In contrast to mammalian and yeast counterparts reported to date, recombinant IDH in Arabidopsis mitochondria did not show adenylate-dependent changes in enzymatic activity. Instead, IDH was inactivated by oxidation treatment and partially reactivated by subsequent reduction. Functional IDH forms a heterodimer comprising regulatory (IDH-r) and catalytic (IDH-c) subunits. IDH-r was determined to be the target of oxidative modifications forming an oligomer via intermolecular disulfide bonds. Mass spectrometric analysis combined with tryptic digestion of IDH-r indicated that Cys128 and Cys216 are involved in intermolecular disulfide bond formation. Furthermore, we showed that mitochondria-localized o-type thioredoxin (Trx-o) promotes the reduction of oxidized IDH-r. These results suggest that IDH-r is susceptible to oxidative stress, and Trx-o serves to convert oxidized IDH-r to the reduced form that is necessary for active IDH complex.